Analisis Manajemen Pihutang dan Profitabilitas pada KPRI Kopergu Bangkalan - Evaliati Amaniyah; Anis Wulandari (BISMA (Bisnis dan Manajemen), 2018)
The purpose of study is to analyze receivable management and profitability at KPRI KOPERGU Bangkalan in 2008-2012. The method used in this study is descriptive method. This study use credit standart, credit terms, credit policy, receivable turnover and credit  riskto analyze receivable management and use return on investment, return on equity and gross profit margin to analyze profitability. The result of this study is receivable tend to decline in 2008-2012 while the strategies of receivable collection is very efective to minimize uncollection receivable. Receivable turnover 1,3 time per year,  ROA 6,44%, ROE 9,47% and gross profit margin18,31%